A novel super-hydrophobic high-strength composite non-woven fabric and preparation method thereof

By using electrospinning and molecular self-assembly technology in superhydrophobic high-strength composite nonwoven fabrics, the fiber layer is prepared and superhydrophobic coating is formed through plasma treatment and nanocoated coating, the problems of nanocoated durability and low temperature flexibility are solved, and the long-term excellent performance of the material in harsh environments is achieved.

CN119754042AInactive Publication Date: 2025-04-04SUZHOU HENGZHUO ESTATE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856777.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The nanocoatings of existing superhydrophobic high-strength composite nonwovens have poor durability and their flexibility decreases in low temperature environments.

Method used

The polypropylene fiber substrate layer was prepared by electrospinning, and the polyethylene terephthalate fiber and aramid fiber reinforced layers were prepared by molecular self-assembly technology. Then, the binding force is increased by plasma treatment or nanocoating coating treatment, a superhydrophobic coating is formed, and the wear resistance and durability of the coating is enhanced by heat treatment or ultraviolet irradiation. At the same time, the addition of graphene nanosheets enhances the conductivity and antistatic properties, aluminum hydroxide or magnesium hydroxide forms a flame retardant layer, enhances the low-temperature flexibility through refrigeration treatment, and adds antioxidants and ultraviolet absorbers to improve weather resistance.

Benefits of technology

It significantly improves the wear resistance and durability of the coating, enhances the flexibility, mechanical strength and flame retardant properties of the material in low temperature environments, and enables non-woven fabrics to maintain excellent performance in harsh environments for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119754042A_ABST
    Figure CN119754042A_ABST
Patent Text Reader

Abstract

The present invention provides a novel super-hydrophobic high-strength composite non-woven fabric and a preparation method thereof, and relates to the field of high-strength composite non-woven fabrics. The novel super-hydrophobic high-strength composite non-woven fabric comprises polypropylene fiber: 50-70%, polyethylene terephthalate fiber: 13-20%, aramid fiber: 7-10%, silicone polymer: 7-10%, fluorinated nanoparticles: 3-5%, intelligent responsive cross-linking agent: 1-3%, nano-silica particles: 0.5-2%, fluorosilane: 0.5-2%, antioxidant: 0.1-1%, ultraviolet absorber: 0.1-1%, lubricant: 0.5-2%, graphene nanosheets: 0.5-2%, flame retardant: 1-3%. The polypropylene fiber is first prepared into a substrate layer by an electrostatic spinning method, and then the polyethylene terephthalate fiber and the aramid fiber are prepared into a reinforcing layer by molecular self-assembly technology, and plasma or nano-coating coating treatment is performed to improve the bonding force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of novel super-hydrophobic high-strength composite non-woven fabrics, in particular to a novel super-hydrophobic high-strength composite non-woven fabric and a preparation method thereof. Background Art

[0002] A new type of super-hydrophobic high-strength composite non-woven fabric is made of polymer materials and nanoparticles. The non-woven fabric is coated with a special nano-coating on the surface, which makes it super-hydrophobic and can effectively prevent water droplets from infiltrating while maintaining good air permeability. In addition, by introducing high-strength fibers, the mechanical properties of the material have been greatly improved, making it excellent in tensile strength and tear resistance. This material is widely used in medical protective clothing, outdoor equipment and high-performance filter materials, showing good application prospects.

[0003] However, this new type of super-hydrophobic high-strength composite nonwoven fabric still has some shortcomings in practical applications. The durability of the nano coating is poor. After long-term use or in harsh environments, the coating may gradually wear out, resulting in a decrease in super-hydrophobic performance. The flexibility of the material decreases in low-temperature environments, which may affect its use in cold regions. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides a novel super-hydrophobic high-strength composite non-woven fabric and a preparation method thereof, which solves the problem of poor durability of the nano coating and the problem of decreased flexibility of the material in a low temperature environment.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: a new type of super-hydrophobic high-strength composite non-woven fabric, comprising:

[0008] Polypropylene fiber: 50-70%, polyethylene terephthalate fiber: 13-20%, aramid fiber: 7-10%, silicone polymer: 7-10%, fluorinated nanoparticles: 3-5%, smart responsive cross-linking agent: 1-3%, nano-silica particles: 0.5-2%, fluorosilane: 0.5-2%, antioxidant: 0.1-1%, UV absorber: 0.1-1%, lubricant: 0.5-2%, graphene nanosheets: 0.5-2%, flame retardant: 1-3%.

[0009] Preferably, the size of the graphene nanosheets is 1-5 microns, and the flame retardant is aluminum hydroxide or magnesium hydroxide.

[0010] Preferably, the particle size of the nano-silica particles is 10-100 nanometers, the fluorosilane is trifluoropropyltrimethoxysilane, the antioxidant is a hindered amine light stabilizer, and the ultraviolet absorber is diphenylbenzotriazole.

[0011] A method for preparing a novel super-hydrophobic high-strength composite non-woven fabric comprises the following steps:

[0012] a. Prepare 50-70% polypropylene fibers into a fiber layer with a diameter of 1-5 microns by electrospinning to form a substrate layer of the non-woven fabric.

[0013] b. 13-20% polyethylene terephthalate fiber and 7-10% aramid fiber are mixed in a mass ratio of 2:1, and a reinforcing layer with a fiber diameter of 5-15 microns is prepared by molecular self-assembly technology, and the reinforcing layer is laminated with the substrate layer.

[0014] c. Plasma treatment or nano-coating treatment is performed on the reinforcement layer to improve the bonding strength between the reinforcement layer and the subsequent coating.

[0015] d. Mix 7-10% of silicone polymer and 3-5% of fluorinated nanoparticles, and add 1-3% of smart responsive cross-linking agent to form a mixed solution.

[0016] e. Add 0.5-2% of nano-silica particles and 0.5-2% of fluorosilane to the mixed solution, and use layer-by-layer self-assembly technology to evenly coat them on the surface of the reinforcement layer to form a super-hydrophobic coating.

[0017] f. The applied coating is subjected to heat treatment or ultraviolet light irradiation to promote cross-linking reaction between the intelligent responsive cross-linking agent and the substrate and the reinforcing layer, thereby enhancing the wear resistance and durability of the coating.

[0018] g. Evenly apply 0.5-2% lubricant on the surface of the cured coating to reduce the surface friction coefficient and further improve the wear resistance.

[0019] h. 0.5-2% of graphene nanosheets are evenly dispersed in the coating material to enhance the conductivity, antistatic properties and mechanical strength of the coating.

[0020] i. Add 1-3% aluminum hydroxide or magnesium hydroxide to the coating to form a flame retardant layer, which significantly improves the flame retardant properties of the non-woven fabric.

[0021] j. Through freezing treatment, the low-temperature flexibility of the coating is enhanced, so that the material can still maintain good mechanical properties and flexibility in low-temperature environments.

[0022] k. Add 0.1-1% hindered amine light stabilizer and 0.1-1% diphenylbenzotriazole to the coating to enhance the material's antioxidant and UV resistance and extend its service life.

[0023] l. Combine all the processed layers and firmly bond them together through heat pressing or ultrasonic welding technology to form the final composite non-woven fabric product.

[0024] Preferably, when the electrospinning method is used to prepare the substrate layer, the voltage used is 15-25 kV to ensure the uniformity and density of the fibers. When the molecular self-assembly technology is used to prepare the reinforcement layer, the temperature and solution concentration are controlled to achieve orderly arrangement of the fibers, thereby enhancing the tear strength of the material.

[0025] Preferably, the plasma treatment time is 30-60 seconds to ensure the bonding force between the reinforcement layer and the coating, and the layer-by-layer self-assembly technology controls the pH value between 4-6 to enhance the bonding effect between the nano-silica particles and fluorosilane.

[0026] Preferably, the intelligent responsive cross-linking agent can be cross-linked and formed within a temperature range of 50-80° C. during the curing process, and the lubricant is polytetrafluoroethylene powder to further reduce the surface friction coefficient.

[0027] Preferably, the flame retardant layer is cured at high temperature to ensure uniform bonding of the flame retardant to the coating, the freezing treatment step is carried out in an environment of -20°C to -40°C to ensure low-temperature flexibility of the coating, and the final molding step is carried out by controlling the hot pressing temperature between 150-180°C to ensure firm bonding of the layers.

[0028] (III) Beneficial effects

[0029] The present invention provides a novel super hydrophobic high-strength composite nonwoven fabric and a preparation method thereof.

[0030] Beneficial effects:

[0031] First, polypropylene fibers are prepared into a base layer by electrospinning, and then polyethylene terephthalate fibers and aramid fibers are prepared into a reinforcement layer by molecular self-assembly technology, and plasma or nano-coating treatment is performed to improve the bonding strength; then, silicone polymers, fluorinated nanoparticles and smart responsive cross-linking agents are mixed to prepare a super-hydrophobic coating, and nano-silica particles and fluorosilane are added for layer-by-layer self-assembly; heat treatment or ultraviolet light irradiation is then performed to cure the coating, and a lubricant is applied to reduce the friction coefficient, and graphene nanosheets are added to enhance the conductivity and antistatic properties of the coating; aluminum hydroxide or magnesium hydroxide is added to form a flame retardant layer, and the low-temperature flexibility of the coating is enhanced by freezing treatment.

[0032] Finally, antioxidants and UV absorbers are added to improve the weather resistance of the material, and the layers are firmly bonded by heat pressing or ultrasonic welding. Through a series of optimization treatments, this preparation method not only improves the wear resistance and durability of the coating, but also enhances the flexibility, mechanical strength and flame retardancy of the material in low temperature environments, enabling the non-woven fabric to maintain excellent performance in harsh environments for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1:

[0036] like Figure 1 As shown, an embodiment of the present invention provides a novel super-hydrophobic high-strength composite non-woven fabric, including: polypropylene fiber: 65.8%, polyethylene terephthalate fiber: 13%, aramid fiber: 7%, silicone polymer: 7%, fluorinated nanoparticles: 3%, smart responsive cross-linking agent: 1%, nano-silica particles: 0.5%, fluorosilane: 0.5%, antioxidant: 0.1%, ultraviolet absorber: 0.1%, lubricant: 0.5%, graphene nanosheets: 0.5%, flame retardant: 1%, the size of the graphene nanosheets is 1-5 microns, the flame retardant is aluminum hydroxide or magnesium hydroxide, the particle size of the nano-silica particles is 10-100 nanometers, the fluorosilane is trifluoropropyltrimethoxysilane, the antioxidant is a hindered amine light stabilizer, and the ultraviolet absorber is dinitrobenzotriazole.

[0037] A method for preparing a novel super-hydrophobic high-strength composite non-woven fabric comprises the following steps:

[0038] a. Prepare 50-70% polypropylene fiber into a fiber layer with a diameter of 1-5 microns by electrospinning to form a non-woven fabric substrate layer. When the electrospinning method is used to prepare the substrate layer, the voltage used is 15-25kV to ensure the uniformity and density of the fiber.

[0039] b. 13-20% polyethylene terephthalate fiber and 7-10% aramid fiber are mixed in a mass ratio of 2:1, and a reinforcing layer with a fiber diameter of 5-15 microns is prepared by molecular self-assembly technology, and the reinforcing layer is laminated with the substrate layer. When the molecular self-assembly technology is used to prepare the reinforcing layer, the temperature and solution concentration are controlled to achieve orderly arrangement of the fibers, thereby enhancing the tear strength of the material. The layer-by-layer self-assembly technology controls the pH value between 4-6 to enhance the bonding effect of nano-silica particles and fluorosilane.

[0040] c. The reinforcing layer is subjected to plasma treatment or nano-coating treatment to improve the bonding strength between the reinforcing layer and the subsequent coating. The plasma treatment time is 30-60 seconds to ensure the bonding strength between the reinforcing layer and the coating.

[0041] d. Mix 7-10% of silicone polymer and 3-5% of fluorinated nanoparticles, add 1-3% of smart responsive crosslinking agent to form a mixed solution. The smart responsive crosslinking agent can be crosslinked and formed within a temperature range of 50-80°C during the curing process.

[0042] e. Add 0.5-2% of nano-silica particles and 0.5-2% of fluorosilane to the mixed solution, and use layer-by-layer self-assembly technology to evenly coat them on the surface of the reinforcement layer to form a super-hydrophobic coating.

[0043] f. The applied coating is subjected to heat treatment or ultraviolet light irradiation to promote cross-linking reaction between the intelligent responsive cross-linking agent and the substrate and the reinforcing layer, thereby enhancing the wear resistance and durability of the coating.

[0044] g. 0.5-2% lubricant is evenly coated on the surface of the cured coating to reduce the surface friction coefficient and further improve the wear resistance. The lubricant is polytetrafluoroethylene powder to further reduce the surface friction coefficient.

[0045] h. 0.5-2% of graphene nanosheets are evenly dispersed in the coating material to enhance the conductivity, antistatic properties and mechanical strength of the coating.

[0046] i. Add 1-3% aluminum hydroxide or magnesium hydroxide to the coating to form a flame retardant layer, which significantly improves the flame retardant properties of the non-woven fabric. The flame retardant layer is cured at high temperature to ensure uniform bonding of the flame retardant and the coating.

[0047] j. Through freezing treatment, the low-temperature flexibility of the coating is enhanced, so that the material can still maintain good mechanical properties and flexibility in a low-temperature environment. The freezing treatment step is carried out in an environment of -20℃ to -40℃ to ensure the low-temperature flexibility of the coating. The final molding step controls the hot pressing temperature between 150-180℃ to ensure the firm bonding of the layers.

[0048] k. Add 0.1-1% hindered amine light stabilizer and 0.1-1% diphenylbenzotriazole to the coating to enhance the material's antioxidant and UV resistance and extend its service life.

[0049] l. Combine all the processed layers and firmly bond them together through heat pressing or ultrasonic welding technology to form the final composite non-woven fabric product.

[0050] Embodiment 2:

[0051] like Figure 1 As shown, an embodiment of the present invention provides a novel super-hydrophobic high-strength composite non-woven fabric, including polypropylene fiber: 39%, polyethylene terephthalate fiber: 20%, aramid fiber: 10%, silicone polymer: 10%, fluorinated nanoparticles: 5%, smart responsive cross-linking agent: 3%, nano-silica particles: 2%, fluorosilane: 2%, antioxidant: 1%, ultraviolet absorber: 1%, lubricant: 2%, graphene nanosheets: 2%, flame retardant: 3%, the size of the graphene nanosheets is 1-5 microns, the flame retardant is aluminum hydroxide or magnesium hydroxide, the particle size of the nano-silica particles is 10-100 nanometers, the fluorosilane is trifluoropropyltrimethoxysilane, the antioxidant is a hindered amine light stabilizer, and the ultraviolet absorber is dinitrobenzimidazole.

[0052] A method for preparing a novel super-hydrophobic high-strength composite non-woven fabric comprises the following steps:

[0053] a. Prepare 50-70% polypropylene fiber into a fiber layer with a diameter of 1-5 microns by electrospinning to form a non-woven fabric substrate layer. When the electrospinning method is used to prepare the substrate layer, the voltage used is 15-25kV to ensure the uniformity and density of the fiber.

[0054] b. 120% polyethylene terephthalate fiber and 10% aramid fiber are mixed in a mass ratio of 2:1, and a reinforcing layer with a fiber diameter of 5-15 microns is prepared by molecular self-assembly technology, and the reinforcing layer is laminated with the substrate layer. When the molecular self-assembly technology is used to prepare the reinforcing layer, the temperature and solution concentration are controlled to achieve orderly arrangement of the fibers, thereby enhancing the tear strength of the material. The layer-by-layer self-assembly technology controls the pH value between 4-6 to enhance the bonding effect between the nano-silica particles and fluorosilane.

[0055] c. The reinforcing layer is subjected to plasma treatment or nano-coating treatment to improve the bonding strength between the reinforcing layer and the subsequent coating. The plasma treatment time is 30-60 seconds to ensure the bonding strength between the reinforcing layer and the coating.

[0056] d. Mix 10% of silicone polymer and 3-5% of fluorinated nanoparticles, add 3% of smart responsive cross-linking agent to form a mixed solution. The smart responsive cross-linking agent can be cross-linked and formed in the temperature range of 50-80°C during the curing process.

[0057] e. Add 0.5-2% of nano-silica particles and 0.2% of fluorosilane to the mixed solution, and use layer-by-layer self-assembly technology to evenly coat them on the surface of the reinforcement layer to form a super-hydrophobic coating.

[0058] f. The applied coating is subjected to heat treatment or ultraviolet light irradiation to promote cross-linking reaction between the intelligent responsive cross-linking agent and the substrate and the reinforcing layer, thereby enhancing the wear resistance and durability of the coating.

[0059] g. 2% lubricant is evenly coated on the surface of the cured coating to reduce the surface friction coefficient and further improve the wear resistance. The lubricant is polytetrafluoroethylene powder to further reduce the surface friction coefficient.

[0060] h. 2% of graphene nanosheets are evenly dispersed in the coating material to enhance the conductivity, antistatic properties and mechanical strength of the coating.

[0061] i. Add 3% aluminum hydroxide or magnesium hydroxide to the coating to form a flame retardant layer, which significantly improves the flame retardant properties of the non-woven fabric. The flame retardant layer is cured at high temperature to ensure uniform bonding of the flame retardant and the coating.

[0062] j. Through freezing treatment, the low-temperature flexibility of the coating is enhanced, so that the material can still maintain good mechanical properties and flexibility in a low-temperature environment. The freezing treatment step is carried out in an environment of -20℃ to -40℃ to ensure the low-temperature flexibility of the coating. The final molding step controls the hot pressing temperature between 150-180℃ to ensure the firm bonding of the layers.

[0063] k. Add 1% hindered amine light stabilizer and 1% dinitrobenzotriazole to the coating to enhance the material's antioxidant and UV resistance and extend its service life.

[0064] l. Combine all the processed layers and firmly bond them together through heat pressing or ultrasonic welding technology to form the final composite non-woven fabric product.

[0065] Table 1: Data comparison table

[0066]

[0067]

[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A novel super hydrophobic high-strength composite nonwoven fabric, characterized in that: include: Polypropylene fiber: 50-70%, polyethylene terephthalate fiber: 13-20%, aramid fiber: 7-10%, silicone polymer: 7-10%, fluorinated nanoparticles: 3-5%, smart responsive cross-linking agent: 1-3%, nano-silica particles: 0.5-2%, fluorosilane: 0.5-2%, antioxidant: 0.1-1%, UV absorber: 0.1-1%, lubricant: 0.5-2%, graphene nanosheets: 0.5-2%, flame retardant: 1-3%.

2. A novel super-hydrophobic high-strength composite nonwoven fabric according to claim 1, characterized in that: The size of the graphene nanosheet is 1-5 microns, and the flame retardant is aluminum hydroxide or magnesium hydroxide.

3. A novel super hydrophobic high-strength composite nonwoven fabric according to claim 1, characterized in that: The particle size of the nano silicon dioxide particles is 10-100 nanometers, the fluorosilane is trifluoropropyltrimethoxysilane, the antioxidant is a hindered amine light stabilizer, and the ultraviolet absorber is diphenylbenzotriazole.

4. A method for preparing a novel super-hydrophobic high-strength composite non-woven fabric, characterized in that: The following steps are involved: a. preparing 50-70% polypropylene fibers by electrospinning into a fiber layer having a diameter of 1-5 microns to form a non-woven fabric substrate layer; b. 13-20% polyethylene terephthalate fiber and 7-10% aramid fiber are mixed in a mass ratio of 2:1, and a reinforcing layer having a fiber diameter of 5-15 microns is prepared by molecular self-assembly technology, and the reinforcing layer is laminated with the substrate layer; c. Plasma treatment or nano-coating treatment is performed on the reinforcement layer to improve the bonding strength between the reinforcement layer and the subsequent coating; d. Mixing 7-10% of silicone polymer and 3-5% of fluorinated nanoparticles, adding 1-3% of smart responsive crosslinker to form a mixed solution; e. Add 0.5-2% of nano-silica particles and 0.5-2% of fluorosilane to the mixed solution, and apply it evenly on the surface of the reinforcement layer using layer-by-layer self-assembly technology to form a super-hydrophobic coating; f. heat treating or irradiating the applied coating with ultraviolet light to promote the cross-linking reaction between the intelligent responsive cross-linking agent and the substrate and the reinforcing layer, thereby enhancing the wear resistance and durability of the coating; g. Evenly apply 0.5-2% lubricant on the surface of the cured coating to reduce the surface friction coefficient and further improve the wear resistance; h. Dispersing 0.5-2% of graphene nanosheets evenly in the coating material to enhance the conductivity, antistatic properties and mechanical strength of the coating; i. Add 1-3% aluminum hydroxide or magnesium hydroxide to the coating to form a flame retardant layer, which significantly improves the flame retardant properties of the non-woven fabric; j. Through freezing treatment, the low-temperature flexibility of the coating is enhanced, so that the material can still maintain good mechanical properties and flexibility in low-temperature environments; k. Add 0.1-1% of hindered amine light stabilizer and 0.1-1% of diphenylbenzotriazole to the coating to enhance the material's antioxidant and UV resistance and extend its service life; l. Combine all the processed layers and firmly bond them together through heat pressing or ultrasonic welding technology to form the final composite non-woven fabric product.

5. The method for preparing a novel super-hydrophobic high-strength composite nonwoven fabric according to claim 4, characterized in that: When the electrospinning method is used to prepare the substrate layer, the voltage used is 15-25 kV to ensure the uniformity and density of the fibers. When the molecular self-assembly technology is used to prepare the reinforcement layer, the temperature and solution concentration are controlled to achieve orderly arrangement of the fibers, thereby enhancing the tear strength of the material.

6. The method for preparing a novel super-hydrophobic high-strength composite nonwoven fabric according to claim 4, characterized in that: The plasma treatment time is 30-60 seconds to ensure the bonding force between the reinforcement layer and the coating. The layer-by-layer self-assembly technology controls the pH value between 4-6 to enhance the bonding effect between the nano-silica particles and the fluorosilane.

7. The method for preparing a novel super-hydrophobic high-strength composite nonwoven fabric according to claim 4, characterized in that: The intelligent responsive cross-linking agent can be cross-linked and formed within a temperature range of 50-80° C. during the curing process, and the lubricant is polytetrafluoroethylene powder to further reduce the surface friction coefficient.

8. The method for preparing a novel super-hydrophobic high-strength composite nonwoven fabric according to claim 4, characterized in that: The flame retardant layer is cured at high temperature to ensure uniform bonding of the flame retardant to the coating, the freezing step is carried out in an environment of -20°C to -40°C to ensure low-temperature flexibility of the coating, and the final molding step controls the hot pressing temperature between 150°C and 180°C to ensure firm bonding of the layers.